Occupational injury prevalence and predictors among small-scale sawmill workers in the Sokoban Wood Village, Kumasi, Ghana. - Felix Agyemang Opoku; Douglas Aninng Opoku; Nana Kwame Ayisi-Boateng; Joseph Osarfo; Alhassan Sulemana; Sheneil Agyemang; Obed Kwabena Offe Amponsah; Michael Tetteh Asiedu; Robert Gyebi; Peter Agyei-Baffour (PLoS ONE, 2024)
Background Sawmill workers are at increased risk of occupational injuries due to their exposure to workplace hazards. However, little is known about the burden of occupational injuries among them in Ghana. Understanding its prevalence and associated factors is necessary to design appropriate interventions to improve workers' health and safety. This study sought to determine the prevalence and factors associated with occupational injuries among small-scale sawmill workers at Sokoban Wood Village, Kumasi. Methods A cross-sectional study was conducted among 138 small-scale sawmill workers from December 2020 to January 2021. Data was collected on demographic and work-related characteristics including age, sex, personal protective equipment (PPE), workspace design, and lighting. The primary outcome was the prevalence of occupational injuries in the 12 months preceding the survey. Logistic regression method was used to assess for independent predictors of occupational injuries, and associations were deemed statistically significant at p < 0.05. Results Approximately 66.7% of the workers experienced occupational injuries within the 12 months preceding the study. Cuts (69.6%) were the most commonly reported injuries. Injuries were mainly caused by machine parts/sharp objects (47.8%) and being hit by logs/objects (46.8%). Only 40.7% of the workers reported always using PPE while legs (38.0%) and hands (37.0%) were the most common body parts injured. The worker's monthly income, poor workspace design and poor lighting had increased odds of occupational injuries while an increase in age was associated with a 5% decreased odds of occupational injuries. Conclusion The prevalence of occupational injuries among the sawmill workers at the Sokoban Wood Village was high, and this calls for prioritization of health and safety at the workplace. Essential measures required include improvements in the safety of machine tools, workspace design and lighting.